2015
DOI: 10.3389/fpls.2015.00016
|View full text |Cite
|
Sign up to set email alerts
|

Control of fire blight (Erwinia amylovora) on apple trees with trunk-injected plant resistance inducers and antibiotics and assessment of induction of pathogenesis-related protein genes

Abstract: Management of fire blight is complicated by limitations on use of antibiotics in agriculture, antibiotic resistance development, and limited efficacy of alternative control agents. Even though successful in control, preventive antibiotic sprays also affect non-target bacteria, aiding the selection for resistance which could ultimately be transferred to the pathogen Erwinia amylovora. Trunk injection is a target-precise pesticide delivery method that utilizes tree xylem to distribute injected compounds. Trunk i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 43 publications
0
72
0
2
Order By: Relevance
“…El ion fosfito es fácilmente transportado en las plantas vía xilema y floema (McDonald et al, 2001;Tkaczyk et al, 2016), por lo que se ha utilizado en aplicación foliar (Rebollar-Alviter et al, 2010;Silva et al, 2011;Pagani et al, 2014;Yáñez et al, 2014;Liljeroth et al, 2016;Borza et al, 2017), baño a la raíz y cuello de la planta (Oka et al, 2007;Akinsanmi y Dreth, 2013), inyección al tronco (Bock et al, 2012;Akinsanmi y Drenth, 2013: Aćimović et al, 2015Aćimović et al, 2016), a través de riego por goteo mezclado en la solución nutritiva en hidroponía (Förster et al, 1998), tratamiento a semilla (Abbasi y Lazarovits 2006; Lobato et al, 2008), aplicación aérea en bajo volumen ) o como tratamiento en inmersión de semillas y frutos (Anderson et al, 2012;Cerioni et al, 2013, Borin et al, 2017Pagani et al, 2014;Yáñez et al, 2014;Liljeroth et al, 2016;Borza et al, 2017), drench of plants root and neck (Oka et al, 2007;Akinsanmi and Dreth, 2013), trunk injection (Bock et al, 2012;Akinsanmi andDrenth, 2013: Aćimović et al, 2015;Aćimović et al, 2016) through drip irrigation mixed in a nutrient solution in hydroponics (Förster et al, 1998), seed treatments (Abbasi and Lazarovits 2006; Lobato et al, 2008), low-volume aerial applications or as a treatment in seed and fruits immersion (Anderson et al, 2012;Cerioni et al, 2013, Bor...…”
Section: Métodos De Aplicaciónunclassified
“…El ion fosfito es fácilmente transportado en las plantas vía xilema y floema (McDonald et al, 2001;Tkaczyk et al, 2016), por lo que se ha utilizado en aplicación foliar (Rebollar-Alviter et al, 2010;Silva et al, 2011;Pagani et al, 2014;Yáñez et al, 2014;Liljeroth et al, 2016;Borza et al, 2017), baño a la raíz y cuello de la planta (Oka et al, 2007;Akinsanmi y Dreth, 2013), inyección al tronco (Bock et al, 2012;Akinsanmi y Drenth, 2013: Aćimović et al, 2015Aćimović et al, 2016), a través de riego por goteo mezclado en la solución nutritiva en hidroponía (Förster et al, 1998), tratamiento a semilla (Abbasi y Lazarovits 2006; Lobato et al, 2008), aplicación aérea en bajo volumen ) o como tratamiento en inmersión de semillas y frutos (Anderson et al, 2012;Cerioni et al, 2013, Borin et al, 2017Pagani et al, 2014;Yáñez et al, 2014;Liljeroth et al, 2016;Borza et al, 2017), drench of plants root and neck (Oka et al, 2007;Akinsanmi and Dreth, 2013), trunk injection (Bock et al, 2012;Akinsanmi andDrenth, 2013: Aćimović et al, 2015;Aćimović et al, 2016) through drip irrigation mixed in a nutrient solution in hydroponics (Förster et al, 1998), seed treatments (Abbasi and Lazarovits 2006; Lobato et al, 2008), low-volume aerial applications or as a treatment in seed and fruits immersion (Anderson et al, 2012;Cerioni et al, 2013, Bor...…”
Section: Métodos De Aplicaciónunclassified
“…Agricultural, urban, and natural tree stands have been the focus of extensive plant pathogen diagnostic and disease management research in recent decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] which recorded an increase in the number of new fungal and bacterial pathogens and their detrimental impact on agroecosystems, ecosystems, and the human society. The economic effects of these pathogens are reflected in lost fresh fruit produce [17][18][19], reduced yields and quality of fruit or wood and cork products [20,21], diminished ecological tree services, and death of whole trees, stands, and forest regions or decimation of fruit industries [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve delivery of an effective pesticide dose, its distribution and expected management of plant detrimental organism or nutrient deficiency, there are several key factors which should be monitored by an applicator as they influence success of trunk injection for these purposes. Besides the plant pathogen biology, ecology, and epidemiology, several factors play a key role in success of trunk injection efficacy: the time of application in relation to detrimental organism establishment and symptom occurrence [11], the season and time of the day of application [41], the chemical properties of pesticide active ingredient and its formulation [42], the injected volume or dose of a pesticide, and the type of tree injection device or technology. For example, a more effective management of plant disease or insect infestation can be achieved by the preventive injections of pesticides in comparison to the therapeutic pesticide applications after the disease or infestation has already occurred.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, the rediscovered and rehabilitated colistin was considered as a final trump (Kádár et al, 2013) until colistin resistance was found in Gram-negative bacterium species, (Otter et al, 2017). Antibiotics are also used in plant medicine (Mc Manus et al, 2002;Stockwell, Sundin and Jones, 2002;Aćimović et al, 2015), but the increasing number of streptomycin-resistant Erwinia amylovora isolates has been causing serious problems both in the USA (Förster et al, 2015) and in Europe (Gusberti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%